2020
DOI: 10.1096/fj.201901981r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen regulates PTEN‐AKT‐mTOR signaling via ROS to alleviate peritoneal dialysis‐related peritoneal fibrosis

Abstract: As a convenient, effective and economical kidney replacement therapy for end‐stage renal disease (ESRD), peritoneal dialysis is available in approximately 11% of ESRD patients worldwide. However, long‐term peritoneal dialysis treatment causes peritoneal fibrosis. In recent years, the application potential of molecular hydrogen in the biomedicine has been well recognized. Molecular hydrogen selectively scavenges cytotoxic reactive oxygen species (ROS) and acts as an antioxidant. In this experiment, a high gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 43 publications
0
31
2
2
Order By: Relevance
“…Oxidative stress triggers inflammatory conditions, including macrophage infiltration in the peritoneum, and mitochondria are a major site for the production of reactive oxygen species (ROS) [6,14,24,25]. As for the mechanism of the effects of MA-5 on mitochondria, previous studies have shown that MA-5 binds to mitofilin, an inner mitochondrial membrane protein, and induces ATP synthase oligomerization, supercomplex formation, and a conformational change in cristae [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative stress triggers inflammatory conditions, including macrophage infiltration in the peritoneum, and mitochondria are a major site for the production of reactive oxygen species (ROS) [6,14,24,25]. As for the mechanism of the effects of MA-5 on mitochondria, previous studies have shown that MA-5 binds to mitofilin, an inner mitochondrial membrane protein, and induces ATP synthase oligomerization, supercomplex formation, and a conformational change in cristae [26].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been reported to cause peritoneal fibrosis via increased oxidative stress [6,[12][13][14], and MA-5 recovers mitochondrial function by reducing oxidative stress in kidney tissues and cardiac myocytes [18]. Therefore, we assessed the mitochondrial component expression level in the peritoneal tissues by performing immunohistochemistry of ATP5a1 and UCP2, both of which play an important role in mitochondrial function (Fig.…”
Section: Ma-5 Restores the Decreased Expression Of Mitochondrial Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Terawaki et al [ 131 ] could reduce peritoneal and systemic oxidative stress without any side effects by single administration of H2-enriched dialysate. Hongtao et al [ 132 ] recently showed that in a mouse model, after the induction of peritoneal fibrosis by a high-glucose solution, treatment with hydrogen-rich peritoneal dialysate exerted an antiperitoneal fibrotic effect, suggested to occur through the ROS/PTEN/AKT/mTOR pathway. These observations highlight the need for H2–PD clinical trials in the future.…”
Section: Strategies Devised To Improve the Biocompatibility Of Pd Solutionmentioning
confidence: 99%
“…Types of PD include intermittent peritoneal dialysis, continuous cycling PD and continuous ambulatory peritoneal dialysis (CAPD). CAPD, a method of uninterrupted dialysis, is one of the main treatment options for end-stage renal disease (Lu et al, 2020). Although CAPD is effective in eliminating metabolic waste and correcting acid, alkali, water and electrolyte-related disorders, it often disrupts daily routines, hinders quality of life and elicits a range of emotional experiences (Ruiz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%